Use of conventional, complementary, and alternative treatments for pain among individuals seeking primary care treatment with buprenorphine-naloxone. - Barry, Declan T; Savant, Jonathan D; Beitel, Mark; Cutter, Christopher J; Moore, Brent A; Schottenfeld, Richard S; Fiellin, David A (Journal of addiction medicine, 2012)
Previous studies have not examined patterns of pain treatment use among patients seeking office-based buprenorphine-naloxone treatment (BNT) for opioid dependence.
Keywords: Adult; Analgesics; Analgesics, Opioid; Buprenorphine; Chronic Pain; Combined Modality Therapy; Comorbidity; Complementary Therapies; Female; Humans; Male; Middle Aged; Naloxone; Narcotic Antagonists; Opiate Substitution Treatment; Opioid-Related Disorders; Primary Health Care; Treatment Outcome; Utilization Review